2021
DOI: 10.1017/jfm.2020.698
|View full text |Cite
|
Sign up to set email alerts
|

Growth and breakup of ligaments in unsteady fragmentation

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 31 publications
(99 reference statements)
4
34
2
Order By: Relevance
“…This canonical fragmentation problem provides fundamental insights regarding when the roles of viscosity and elasticity must be incorporated explicitly and when they can be neglected for their effect on the spray of interest. Indeed, in the Newtonian inviscid limit, the droplet size and speed distributions can be predicted exactly and are given by a superposition of Gaussian distributions with time-varying mean, with smaller and faster droplets shed early in the unsteady process and larger and slower droplets shed later (17,124). Therefore, the unsteadiness of the fragmentation process inherently causes the observed skewness of the droplet size and speed distributions.…”
Section: Canonical Axisymmetric Unsteady Fragmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…This canonical fragmentation problem provides fundamental insights regarding when the roles of viscosity and elasticity must be incorporated explicitly and when they can be neglected for their effect on the spray of interest. Indeed, in the Newtonian inviscid limit, the droplet size and speed distributions can be predicted exactly and are given by a superposition of Gaussian distributions with time-varying mean, with smaller and faster droplets shed early in the unsteady process and larger and slower droplets shed later (17,124). Therefore, the unsteadiness of the fragmentation process inherently causes the observed skewness of the droplet size and speed distributions.…”
Section: Canonical Axisymmetric Unsteady Fragmentationmentioning
confidence: 99%
“…The axisymmetric unsteady fragmentation process resulting from the impact of a droplet on a target of comparable size (Figure 8m,n) results in rich, coupled, spatially and temporally varying, multiscale, nonlinear processes that can be broken down into sheet and rim evolution and determination of droplet size and speed distributions (17,124). Upon impact, the droplet is transformed into a rapidly expanding two-dimensional fluid sheet whose rim continuously destabilizes, generating fluid ligaments that, in turn, destabilize and shed droplets, mostly one at a time throughout the sheet expansion process.…”
Section: Canonical Axisymmetric Unsteady Fragmentationmentioning
confidence: 99%
“…Figures 1(b) and 2 show that the contour of the liquid sheet in unsteady fragmentation is nearly circular in contrast to the cusp-containing shape of stationary sheets (Gordillo et al 2014). In the interest of concision, details on how rim deceleration induces fluid shedding during cusp-free unsteady sheet fragmentation discussed by Wang & Bourouiba (2021) are not repeated here.…”
Section: Review Of Unsteady Sheet Evolutionmentioning
confidence: 99%
“…We/Re can be used to indicate the relationship between the inertial, capillary and viscous forces. The detailed mechanism of the ejection of secondary droplets from the crown and the effects of the impact parameters on the size of the secondary droplets are mainly studied at standard environmental pressure [26][27][28][29][30][31] . Different models have been proposed to explain the splashing mechanisms at standard environmental pressure, such as rim instability 26,[28][29][30][31] , eject sling-shot 32 , crown breakup 27 , and levitated viscous sheet 33,34 .…”
Section: Introductionmentioning
confidence: 99%
“…The detailed mechanism of the ejection of secondary droplets from the crown and the effects of the impact parameters on the size of the secondary droplets are mainly studied at standard environmental pressure [26][27][28][29][30][31] . Different models have been proposed to explain the splashing mechanisms at standard environmental pressure, such as rim instability 26,[28][29][30][31] , eject sling-shot 32 , crown breakup 27 , and levitated viscous sheet 33,34 . Roisman et al 30 studied the formation and growth of disturbance in the rim centerline by the transverse rim instability and found that the diameter of the fingers was similar to the size of the rim and also similar to the diameter of the outermost secondary droplets.…”
Section: Introductionmentioning
confidence: 99%